THE CUSTOMERS BEHAVIORAL INTENTION TO SELECT ISLAMIC BANKING IN INDONESIA - Reni, Andi (Universitas Islam Negeri Alauddin Makassar, 2015)
Indonesia is the largest number of Muslimspopulate, the market share of Islamic banking in Indonesia is only 3.2 percent of its total banking system. Hence, the quest to attract a large number of customers is a major challenge to Indonesian banks. However, few studies use Theory of Reasoned Action (TRA)to identify factors which significantly influence customers’ intention to use and select Islamic banking for their banking transactions. This paper investigates the constructs of TRA, add variable religiosity on Islamic banking selection. The study employed questionnaires to 275 respondents of bank customers in Palembang , Jakarta, and Makassar are represented big regions of Indonesia. Using Partial Least Square Structural Equation Modelling , attitude, subject norm,and religion are statistically significant effect on intention to select Islamic bank in Indonesia. The model explains 43 % of the total variance in Islamic banking intention. The results imply that Indonesian Islamic banks should strategize ways to develop positive attitude and reference amongst their customers through greater dissemination of knowledge about Islamic banking while emphasizing on the religious compliance.